An integral equation involving the confluent hypergeometric function of several complex variables - Srivastava, H. M. (Applicable analysis, 1976)
In the present note the author establishes an inversion theorem for a convolution transform whose kernel involves a confluent hypergeometric function of several complex variables. It is shown how the main result can be specialized to solve a number of integral equations involving special functions of interest in applied problems. An extension of the method to a general class of integral equations is also considered.